In‐Flight Observation of Gamma Ray Glows by ILDAS. Issue 23 (4th December 2017) - Kochkin, Pavlo; van Deursen, A. P. J.; Marisaldi, M.; Ursi, A.; de Boer, A. I.; Bardet, M.; Allasia, C.; Boissin, J.‐F.; Flourens, F.; Østgaard, N.
Abstract: An Airbus A340 aircraft flew over Northern Australia with the In‐Flight Lightning Damage Assessment System (ILDAS) installed onboard. A long‐duration gamma ray emission was detected. The most intense emission was observed at 12 km altitude and lasted for 20 s. Its intensity was 20 times the background counts, and it was abruptly terminated by a distant lightning flash. In this work we reconstruct the aircraft path and event timeline. The glow‐terminating flash triggered a discharge from the aircraft wing that was recorded by a video camera operating onboard. Another count rate increase was observed 6 min later and lasted for 30 s. The lightning activity as reported by ground networks in this region was analyzed. The measured spectra characteristics of the emission were estimated. Key Points: Two gamma ray glows were observed at 12 km altitude over Northern Australia The observation was conducted by the In‐flight Lightning Damage Assessment System (ILDAS) Gamma ray glow was terminated by a distant lightning flash